1963
DOI: 10.1017/s0016672300003852
|View full text |Cite
|
Sign up to set email alerts
|

Cellular damage associated with multiple mating inE. coli

Abstract: In crosses in which the ratio of Hfr to F- cells was varied it was found that with one group of Hfr strains the yield of recombinants increased linearly with donor concentration until the number of donor and recipient cells were approximately equal. With other Hfr strains marked deviations from linearity were observed at Hfr: F−ratios greater than 1:5 and in crosses with one particular F−strain the yield of recombinants actually decreased progressively as the Hfr concentration was raised beyond this value. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1964
1964
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Two further lethal phenomena are connected with conjugative plasmids: lethal zygosis (Gross, 1963) and zygotic induction (Hayes, 1965) are associated with plasmid transfer by conjugation. Lethal zygosis was first observed as reduced viability of the recipients under conditions where F − bacteria were used in matings with an excess of Hfr donor cells (carrying F factor integrated into their chromosome).…”
Section: Other Phenotypes Associated With Bacterial Plasmidsmentioning
confidence: 99%
“…Two further lethal phenomena are connected with conjugative plasmids: lethal zygosis (Gross, 1963) and zygotic induction (Hayes, 1965) are associated with plasmid transfer by conjugation. Lethal zygosis was first observed as reduced viability of the recipients under conditions where F − bacteria were used in matings with an excess of Hfr donor cells (carrying F factor integrated into their chromosome).…”
Section: Other Phenotypes Associated With Bacterial Plasmidsmentioning
confidence: 99%
“…Recipients are killed only when mated with large numbers of donors (with a donor-to-recipient ratio of about 20:1), although there are bacteriostatic effects at lower multiplicities. The lethal effects of a high multiplicity of donors have been reported several times (5,85,213,421), and the mechanism has recently been investigated in detail by Skurray and Reeves (529,530,531).…”
Section: Comparable Effects Of Other Proteinsmentioning
confidence: 99%
“…As the Hfr concentration was increased, the yield of recombinants (24) and the survival of F-cells (8) decreased. These observations led to the suggestion that the lethality observed could result from multiple conjugation involving simultaneous mating between one Fcell and several Hfr cells (8,24).…”
mentioning
confidence: 99%
“…As the Hfr concentration was increased, the yield of recombinants (24) and the survival of F-cells (8) decreased. These observations led to the suggestion that the lethality observed could result from multiple conjugation involving simultaneous mating between one Fcell and several Hfr cells (8,24). There have been comments on the phenomenon in a number of reviews and reports (25,27,32,37,41), but no further detailed studies have been reported, and as a preliminary to examining recipient cells for metabolic changes associated with the lethal event, the phenomenon was characterized.…”
mentioning
confidence: 99%